New state and host records for Agromyzidae (Diptera) in the United States, with the description of thirty new species - Eiseman, Charles S.; Lonsdale, Owen (Zootaxa, 2018)
We present rearing records of Agromyzidae (Diptera) from five years of collecting throughout the United States. We review host and distribution data, and describe leaf mines, for 93 species, plus 28 others that could not be confidently identified in the absence of male specimens. We report 147 new host species records, including the first rearing records for Agromyza bispinata Spencer, A. diversa Johnson, A. parca Spencer, A. pudica Spencer, A. vockerothi Spencer, Calycomyza michiganensis Steyskal, Ophiomyia congregata (Malloch), and Phytomyza aldrichi Spencer. Phytomyza anemones Hering and (tentatively identified) Cerodontha (Dizygomyza) iraeos (Robineau-Desvoidy) are new to North America; Agromyza albitarsis Meigen, Amauromyza shepherdiae Sehgal, Aulagromyza populicola (Walker), Liriomyza orilliensis Spencer, Phytomyza linnaeae (Griffiths), P. solidaginivora Spencer, and P. solidaginophaga Sehgal are new to the USA. We also present confirmed USA records for Calycomyza menthae Spencer (previous records were based only on leaf mines), Ophiomyia maura (Meigen) (reported from the USA in older literature but deleted from the fauna in the most recent revision (Spencer & Steyskal 1986)), and Phytomyza astotinensis Griffiths and P. thalictrivora Spencer (previously only tentatively recorded from the USA). We provide 111 additional new state records. We describe the following 30 new species: Agromyza fission, A. soka, Melanagromyza palmeri, Ophiomyia euthamiae, O. mimuli, O. parda, Calycomyza artemisivora, C. avira, C. eupatoriphaga, C. vogelmanni, Cerodontha (Dizygomyza) edithae, Cer. (D.) feldmani, Liriomyza ivorcutleri, L. valerianivora, Phytomyza actaeivora, P. aesculi, P. confusa, P. doellingeriae, P. erigeronis, P. hatfieldae, P. hydrophyllivora, P. palmeri, P. palustris, P. sempervirentis, P. tarnwoodensis, P. tigris, P. triangularidis, P. vancouveriella, P. verbenae, and P. ziziae.